2019
DOI: 10.1080/19475705.2019.1690058
|View full text |Cite
|
Sign up to set email alerts
|

A Sentinel-1-based clustering analysis for geo-hazards mitigation at regional scale: a case study in Central Italy

Abstract: In the last decade satellite remote sensing has become an effective tool for monitoring geo-hazard-induced ground motions, and has been increasingly used by the scientific community. Direct and indirect costs due to geo-hazards are currently rising, causing serious socio-economics and casualty losses. Therefore, creating a priority list turns out to be essential to highlight the most relevant ground deformations and to better focus risk management practices at regional scale. The Sentinel-1 constellation, than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Consequently, the promising results obtained by the scientific community and the free availability of data, which permit drastic cost reductions, have drawn increasing interest from the administrative managing office for the mapping and monitoring of the ground deformation issue [223][224][225].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the promising results obtained by the scientific community and the free availability of data, which permit drastic cost reductions, have drawn increasing interest from the administrative managing office for the mapping and monitoring of the ground deformation issue [223][224][225].…”
Section: Discussionmentioning
confidence: 99%
“…The three main products provided by the EGMS are: (i) the ground deformation maps and time-series along the LOS direction; (ii) an advanced ground deformation map in LOS direction combined with the GNSS data of the EUREF permanent network (EPN) [227]; and (iii) the two main deformation components derivable from the combination of the two orbits, i.e., the horizontal East-West and the vertical up-down deformation. All these products will be updated annually and will open several other opportunities for investigation with a consequent advancement in the knowledge in various fields, e.g., ground deformation prediction [228], mapping [224,225,229], and monitoring [230] of natural hazards, and atmospheric delay analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The concept has been developed by Bianchini et al [132] and further improved by Barra et al [177]. In Italy, the hot-spot mapping approach has been applied in the Valle d'Aosta [73,74] and Tuscany [178][179][180] regions. More complex clustering approaches were proposed by Milone & Scepi in the Avellino (Campania region) area (CLARA, Clustering LARge Application algorithm [181]) and by Lu et al [35,37,182] for the Arno River Basin and the Volterra municipality (Tuscany region).…”
Section: Landslide Mappingmentioning
confidence: 99%
“…However, the use of this tool has grown significantly to identify and monitor known geothermal systems to evaluate and also discover new geothermal systems, selecting the best sites and strategies for developing engineering geothermal systems, and reducing drilling and investment risks in proposed systems (Faulds and Hinz, 2015). Various studies in different fields such as heat flux mapping, geo-hazard mitigation (Montalti et al, 2019), and surface deformation in geothermal sites (Lubitz et al, 2013) can be found (Vasco et al, 2013).…”
Section: Geothermal Potential Assessmentmentioning
confidence: 99%